Research advances in the role of endogenous neurogenesis on neonatal hypoxic-ischemic brain damage - Chen, Andi; Chen, Xiaohui; Deng, Jianhui; Zheng, Xiaochun (Frontiers in Pediatrics, 2022)
Hypoxic-ischemic brain damage (HIBD) is a main cause of perinatal mortality and neurologic complications in neonates, but it remains difficult to cure due to scarce treatments and complex molecular mechanisms remain incompletely explained. Recent, mounting evidence shows that endogenous neurogenesis can improve neonatal neurological dysfunction post-HIBD. However, capacity for spontaneous endogenous neurogenesis is limited and insufficient for replacing neurons lost to brain damage. Therefore, it is of great clinical value and social significance to seek therapeutic techniques that promote endogenous neurogenesis, to reduce neonatal neurological dysfunction from HIBD. This review summarizes the known neuroprotective effects of, and treatments targeting, endogenous neurogenesis following neonatal HIBD, to provide new targets and directions and a theoretical basis for the treatment of neonatal neurological dysfunction from HIBD.